Comparative Assessment of Immune Cell Subset Ratios (NKT/NK, Th/Tc, B1/B2) in Gestational Diabetes and Healthy Pregnancy: Links to Biochemical and Immunochemical Profiles - Jelena Omazić; Andrijana Muller; Mirta Kadivnik; Blaženka Dobrošević; Barbara Vuković; Mirela Florijančić; Jasenka Wagner (Metabolites)
Introduction: Gestational diabetes (GD) is a common pregnancy metabolic disorder involving immune alterations. While there is a link between immune cells and GD, the specific roles of NKT/NK, helper/cytotoxic T, and B1/B2 lymphocyte ratios in complicated/uncomplicated pregnancies with and without GD are underexplored. This cross-sectional study hypothesized that specific imbalances in these lymphocyte ratios would be present in GD, and that these ratios would correlate with key metabolic parameters in pregnancy. Methods: We compared these lymphocyte ratios in 162 third-trimester pregnant women across four groups: healthy uncomplicated (n = 40), healthy complicated (n = 40), GD uncomplicated (n = 42), and GD complicated (n = 40), using flow cytometry and by measuring biochemical parameters. Results: No significant differences in lymphocyte ratios were found between GD and healthy pregnancies. Novel correlations emerged: in the entire cohort, the NKT/NK ratio positively correlated with C-peptide and triglycerides, and negatively with HDL cholesterol. The helper/cytotoxic ratio negatively correlated with insulin and C-peptide. In the GD group, NKT/NK correlated positively with C-peptide, and helper/cytotoxic negatively with insulin. Conclusion: These findings suggest a subtle yet significant link between immune cell subsets and metabolic status in pregnancy and GD, warranting further investigation.